Flexible, All‐Inorganic CsPbBr3 Perovskite Solar Cells Tailored by Heat‐resistant Muscovite Substrates. Issue 6 (10th February 2021) - Xu, Yafeng; Duan, Jialong; Du, Jian; Yang, Xiya; Duan, Yanyan; Tang, Qunwei
Abstract: All‐inorganic CsPbBr3 perovskite solar cells (PSCs) have attracted tremendous attention, owing to their excellent stability and rising power conversion efficiency. However, the mechanical flexibility of these solar cells has ground to a standstill because of the high‐temperature requirement for ideal CsPbBr3 perovskite films. In this study, a flexible CsPbBr3 PSC with an efficiency of 5.71 % has been made by means of fabricating a heat‐resistant conductive muscovite substrate, which demonstrates very high mechanical flexibility with nearly unchanged resistance even after 4000 bending cycles (12000 cycles of concave and convex bending for PSCs), owing to the weak van der Waals force and layered structure. Implementation of the muscovite substrate enables the fabrication of flexible PSCs under high‐temperature conditions, providing a new path to increase the efficiency without lowering the crystallization temperature of state‐of‐the‐art electron‐transporting materials and perovskite films in the future. Abstract : Bend me, shape me : A flexible, all‐inorganic CsPbBr3 perovskite solar cell with a power conversion efficiency of 5.71 % has been fabricated based on a heat‐resistant conductive muscovite substrate. The device shows high mechanical flexibility, with no performance degradation after 12000 cycles of concave and convex bending at 1.0 mm curvature.